2020
DOI: 10.3390/chemistry2010007
|View full text |Cite
|
Sign up to set email alerts
|

Uranyl Ion Complexes of Polycarboxylates: Steps towards Isolated Photoactive Cavities

Abstract: Consideration of the extensive family of known uranyl ion complexes of polycarboxylate ligands shows that there are quite numerous examples of crystalline solids containing capsular, closed oligomeric species with the potential for use as selective heterogeneous photo-oxidation catalysts. None of them have yet been assessed for this purpose, and some have obvious deficiencies, although related framework species have been shown to have the necessary luminescence, porosity and, to some degree, selectivity. Aspec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 118 publications
0
6
0
Order By: Relevance
“…[ 8 ] In the particular case of cavity‐defining, uranyl‐containing polynuclear discrete species or porous frameworks, applications as selective heterogeneous photo‐oxidation catalysts [ 9 ] could be contemplated. [ 10 ] Indeed, several reports describe photocatalytic uses of uranyl‐containing frameworks, [ 11 ] particularly for degradation of pollutants. In this regard, uranyl complexes with high solid state photoluminescence quantum yields (PLQYs) are highly desirable, but these values are seldom reported and, when they are measured, they are often low.…”
Section: Introductionmentioning
confidence: 99%
“…[ 8 ] In the particular case of cavity‐defining, uranyl‐containing polynuclear discrete species or porous frameworks, applications as selective heterogeneous photo‐oxidation catalysts [ 9 ] could be contemplated. [ 10 ] Indeed, several reports describe photocatalytic uses of uranyl‐containing frameworks, [ 11 ] particularly for degradation of pollutants. In this regard, uranyl complexes with high solid state photoluminescence quantum yields (PLQYs) are highly desirable, but these values are seldom reported and, when they are measured, they are often low.…”
Section: Introductionmentioning
confidence: 99%
“…The value for 1 exceeds that measured under the same conditions for uranyl nitrate hexahydrate (24%), and it is among the largest found in a uranyl carboxylate complex, other large values having been found in some complexes with (1R,3S)-(+)-camphorate (23%), 83 dipicolinate (42%), 83 succinate (49%), 84 and 1,3,5benzenetricarboxylate (58%). 7 Such large PLQY values are a requisite in the prospect of using uranyl ion complexes containing isolated cavities as photoactive devices, 85 but as seen in the present examples, these may vary widely for solids of similar composition and structure, indicating that subtle effects may have a strong influence, and it remains unclear as to how to maximize this parameter.…”
Section: ■ Results and Discussionmentioning
confidence: 90%
“…The high oxophilicity [1] of uranium(VI), reflected basically in the nature of its wellknown form as that of uranyl ion, UO2 2+ [2], as well as in the difficulty of obtaining the simple aza-analogue of this cation [3], remains operative in the secondary coordination interactions which give rise to the array of donor atoms lying close to one plane perpendicular to the linear O-U-O unit and found almost universally in compounds regarded formally as containing the uranyl cation [2,4]. X-ray crystallographic studies, especially numerous in the case of carboxylate species [5,6,7], have shown that in the solid state this "equatorial garland" may contain different numbers of donor atoms varying between three (e.g. [HNEt3][UO2(hexahomotrioxacalix [3]arene -3H)] and related species [8,9] and [Na(thf)2][UO2{N(SiMe3)2}3] [10]) and six (e.g.…”
Section: Introductionmentioning
confidence: 99%
“…The U(VI) aqua ion has been shown to have a pentagonal-bipyramidal form as [UO2(OH2)5] 2+ in both the solid state and solution through XRD [12][13][14] and EXAFS measurements allied to computational studies [14][15][16] but what is very obvious in the crystal structure determinations is that this cation is involved in multiple H-bonding interactions with its environment, raising the question as to what influence such interactions may have on the equatorial coordination number. While H-bonding is certainly well-recognised as a factor influencing solid state structures of uranyl ion carboxylate complexes in particular [5,6,7], as well as in less abundant species (e.g. phosphonates [17]), it has not usually been assessed in terms of any influence upon the equatorial coordination sphere.…”
Section: Introductionmentioning
confidence: 99%